Strategy Coaching Clinic Solutions Improving Teacher Ability in Writing Scientific Publication - Munajah, Robiatul; Budiana, Kiki (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
The teacher is a professional. As a consequence of the position of teacher as a profession, a system of guidance and development of the teaching profession is needed that is programmed and sustained through professional development activities. However, based on field studies, most teachers have difficulty in writing scientific papers, so it is necessary to develop a coaching model that can improve the ability of teachers to compile scientific papers in the form of scientific publications. The formulation of the problem in the research is whether the Guidance Strategy Coaching Clinic can increase the activity of writing scientific publications of teachers at the Teacher Work Centers (PKG) of Kaduhejo Pandeglang subdistrict? Guidance Strategy Coaching Clinic can increase the interest in writing scientific publications of teachers at the Kaduhejo Pandeglang subdistrict Teacher Training Center (PKG) and Guidance Strategy can the Coaching Clinic Improve the quality of teacher scientific publications at the Kaduhejo Pandeglang subdistrict Teacher Training Center (PKG)? This study uses an action research design (Action Research) because this study addresses the practice of writing scientific publications, the problem of fostering the teaching profession concerning the improvement and improvement of writing competence. Action research is a form of study carried out to improve the conditions of teacher coaching and mentoring practices. Through the use of Guidance Strategies Coaching Clinic in the Guidance and professional development activities of teachers can increase the activities of writing scientific publications. This can be seen from the average percentage in the first cycle of 59.38%, increasing 28.75% in the second cycle to 88.13%. Interest in writing scientific publications of teachers increases. This can be seen from the final score in the first cycle of 3.58 experiencing an increase in the second cycle of 0.09 to 3.67. Then through the use of the Guidance Strategy, Coaching Clinic can improve the results of writing scientific publications of teachers at the Kaduhejo District Teacher Training Center (PKG). This can be seen from the average test results in the first cycle of 71.41, an increase of 5.62 in the second cycle to 77.03. Similarly, the percentage of mastery learning has increased from 59.38% to 37.50% increase to 96.88%. Guiding Strategy Coaching Clinic should be implemented according to the needs, gradually, continuously to improve the professionalism of the teacher